High-Velocity Shear and Soft Friction at the Nanometer Scale - Thorén, Per-Anders; Borgani, Riccardo; Forchheimer, Daniel; Haviland, David B. (Frontiers in Mechanical Engineering, 2021)
We study high-speed friction on soft polymer materials by measuring the amplitude dependence of cyclic lateral forces on the AFM tip as it slides on the surface with fixed contact force. The resulting dynamic force quadrature curves separate the elastic and viscous contributions to the lateral force, revealing a transition from stick-slip to free-sliding motion as the velocity (amplitude of lateral motion) is increased. We explain force quadratures, describe how they are measured, and we show results for a variety of soft materials. The results differ substantially from measurements on hard materials, showing hysteresis in the force quadrature curves that we attribute to the finite relaxation time of a visco-elastic surface deformation.